MAJLIS TAFSIR AL-QUR’AN DAN KEBERAGAMAAN DI INDONESIA: STUDI TENTANG PERAN DAN KEDUDUKAN HADIS MENURUT MTA - Suryadilaga, Muhammad Alfatih (Masyarakat Indonesia, 2015)
Social development of Muslim society in Indonesia related to the study of hadith seems quite dynamic. Each organization has its own characteristics in defining and positioning hadith as the second of Islamic authority after Qur’an, such as the Majlis Tafsir Al-Qur’an (MTA). The problem begun since there is a research mentioning that MTA is almost considered not positioning hadith as explanatory of Qur’an. It is dealing with the MTA jargon its self, returning to the Qur’an and sunnah shahihah. This article discusses about how MTA, which is currently led by Ahmad Sukino, positions the hadith as the second of Islamic authority after Qur’an. In addition, MTA states that only sunah shahihah can be used as dalil or hujjah. MTA also distinguishes human cultural behaviors with pure religious behaviors as they are generally called ‘ibadah. Thus, for MTA, no ‘ibadah except there is nash sharih, both from the Qur’an and sunnah. Then, when we read more deeply and critically, MTA is actually inconsistent in understanding and practicing Islam textually, but sometimes they use the fikih and usul fikih as a means to analyse the Qur’an and hadith.